[Ktavim nivkharim. Selected writings. Ed. by M. Buber. Transl. by Y. Keshet] (Hasifriah hatsionit)
With index. Text in Hebrew. 1. Ktavim tsioniyim vihudiyim. [Zionist writings; incl. a transl. of "Rom und Jerusalem"]. 1954. II, 256 p. - With ills and prt.